Globalized arts : the entertainment economy and cultural identity - Singh, J. P., 1961- (Columbia University, 2011)
Our interactive world can take a cultural product, such as a Hollywood film, Bollywood song, or Latin American telenovela, and transform it into a source of cultural anxiety. What does this artwork say about the artist or the world she works in? How will these artworks evolve in the global market? Film, music, television, and the performing arts enter the same networks of exchange as other industries, and the anxiety they produce informs a fascinating area of study not only for art and culture but also for global politics. Focusing on the confrontation between global politics and.